Assembly of the Annieopsquotch Accretionary Tract, Newfoundland Appalachians: Age and Geodynamic Constraints from Syn‐Kinematic Intrusions - Lissenberg, Cornelis Johan; Zagorevski, Alexandre; McNicoll, Vicki J.; van Staal, Cees R.; Whalen, Joseph B. (The Journal of Geology, 2005)
The Annieopsquotch Accretionary Tract (AAT) comprises several ophiolites and arc‐back‐arc igneous complexes that were accreted to the Dashwoods microcontinent during the Ordovician Taconic orogeny. The Lloyds River Fault Zone, which separates the AAT from the Dashwoods microcontinent, yielded 40Ar/39Ar hornblende ages of ca. 470 Ma. The fault zone was intruded syn‐kinematically by the shoshonitic Portage Lake monzogabbro and the Pierre’s Pond suite, which gave U/Pb zircon ages of Ma plus Ma and Ma, respectively. The Otter Pond granodiorite intruded syn‐kinematically into the Otter Brook Shear Zone, which separates the Annieopsquotch ophiolite belt from the structurally underlying ophiolitic Lloyds River Complex. It yielded a U/Pb zircon age of Ma. The Buchans arc and its continental basement were accreted to the Lloyds River Complex prior to 468 Ma. Syn‐kinematic plutons have arc affinity, with εNd ranging between −0.9 and −6.8, and are coeval with the adjacent Notre Dame Arc. Our data thus suggest the majority of the AAT was accreted to the Dashwoods microcontinent by 468 Ma, when consanguineous, dominantly arclike plutons intruded within the AAT and adjacent Notre Dame Arc. The Portage Lake monzogabbro and Otter Pond mafic suite are more mafic than Notre Dame Arc plutons of similar age because of their intrusion into the thin, mafic crust of the AAT and ascent along shear zones. Our data indicate the formation and subsequent accretion of ophiolites and arc‐back‐arc complexes occurred within a very short time span (5–10 Ma). The sources of AAT syn‐orogenic magmatism are diverse and include melting of subarc mantle during slab breakoff, lithospheric mantle, and lower crust. The Ordovician Appalachian margin of Laurentia grew by the accretion of oceanic terranes and intrusion of mantle‐derived magma. Recycling of continental crust by rifting and subsequent collision played an important part of the tectonic evolution of the AAT.